A Community-Based Intervention for Mental Health and Wellbeing in Pregnancy and Postpartum: One Healthy Start Site’s Story - Sampson M; Xu W; York FN; Roberson J (International Journal of Women's Health)
McClain Sampson,1 Wen Xu,2 Felicia N York,3 Jerry Roberson4 1Graduate College of Social Work, University of Houston, Houston, TX, USA; 2Department of Innovative Social Work, Faculty of Health and Wellbeing, City University of Macau, Macao, SAR, People’s Republic of China; 3Texas A&M University, College Station, TX, USA; 4United Associates, Dallas, TX, USACorrespondence: McClain Sampson, Graduate College of Social Work, University of Houston, Houston, TX, USA, Email mmsampson@uh.eduPurpose: Perinatal mood and anxiety disorders (PMADs) are the leading cause for maternal morbidity and are associated with underlying causes of pregnancy-related death. Healthy Start (HS) programs around the country seek to lower the risk of maternal mortality through services that screen for and address social determinants of health, including mental health. This study used secondary data from the University of Houston Healthy Start (UHHS) to examine postpartum depression screening and referral rates among program participants and feedback from participating mothers about the program’s mental health services.Patient and Methods: Secondary quantitative data from the program’s administration of services (n = 164) and secondary qualitative data from a sub-set of program participants (n = 23) were analyzed. Using data from the standardized HS tools (required for all sites), aggregate demographic data and screening results of depression and interpersonal violence were assessed. Anonymous qualitative data from focus groups were analyzed for themes related to mental health.Results: Screening for postpartum depression was 97% with a 78% referral rate. Screening for interpersonal violence (IPV), a known correlate of PMADs, was 98% with a 100% referral rate for the 4 women who screened positive for IPV. Qualitative themes revealed close-knit relationships with case managers and doulas that encouraged disclosure of symptoms, honest discussions, and an increased desire to ask for help when needed. Emergent themes revealed that Persistence and authenticity were critical to gain participant trust; a culture of sisterhood positively participants’ mental health; and case managers were proactive with emotional support and resource referral.Conclusion: High rates of mental health screening and referral at the UHHS site were documented and participant stories revealed that trust with case managers was instrumental to their wellbeing. More robust data is needed to allow statistical comparisons are needed in future research.Plain Language Summary: In this study, we wanted to know how well a strengths-based program, the University of Houston Healthy Start (UHHS), screened and referred mothers for postpartum depression needs. We also want to explore how mothers in the program perceived and experienced mental health services provided by UHHS. We used existing data from the program evaluation to answer both questions.We analyzed administrative data from 164 mothers in the program and analyzed anonymous qualitative data from focus groups (n=). We found that nearly all mothers (97%) were screened for postpartum depression, and among high-risk moms, the majority (78%) got referrals for further care. From the group interviews, we learned that mothers formed strong, trusting relationships with case managers. This close bond encouraged them to open up about their struggles and seek help. Positive stories shared in focus groups convey the importance of the relationship between case manager and program participant.Keywords: perinatal, community home-visiting, depression